Increase of Social Impact Due to the Development of the Renewable Energy Industry in Russia - Nazarova, Yulia Alexandrovna; Sopilko, Natalya Yuryevna; Bolotova, Rimma Shoidorzhievna; Shcherbakova, Natalya Sergeevna; Alexeenko, Vladimir Borisovich (International Journal of Energy Economics and Policy, 2017)
The article is providing highlights on the development prospects of the renewable energy industry in Russia from the point of view of increasing the social impact on jobs creation. The branch of renewable energy is considered as one of the directions reducing unemployment in the regions of Russia. The peculiarities of the industry development in Russia, related to the existing regulatory and legal framework and the structure of the national electric power market, are singled out. As a result of the study, methodological approaches in assessing the social effect from the development of the renewable energy industry in Russia are formulated. Also a forecast of the number of created jobs is made, taking into account the implementation of projects in the wholesale and retail electric power markets and isolated power systems. The compiled statistical and expert data allow to develop scenarios for commissioning capacities in the industry. The proposed approaches and scenarios make it possible to estimate the number of created jobs regionally and analyze the impact of these places on the level of unemployment in the regions of Russia. Regions have been identified where the development of the renewable energy sector will have a significant positive social effect. Quantitative assessment of the social effects of the industry development can help to work out mechanisms of state support for renewable energy, for performing technical and economic calculations for projects and regional programs in the field of renewable resources and energy sources. The results can be used to formulate criteria for regional competitive selection, to formulate schemes for the territorial development of the electric power industry. Keywords: Renewable energy industry, social effect, unemployment level, Russian regions, jobs creation JEL Classifications: J21, J60, L72